Modified Extensive Culture of Penaeus monodon Using Indigenous Feed - Jose, Susheela; K.G., Ramachandran Nair; P.T., Mathew; Stephen, Jose; P., Madhavan (Fishery Technology, 2025)
Short-term monoculture of Penaeus monodon was done using an indigenously developed feed to evaluate the efficiency of the feed with respect to growth, survival, production, food conversion ratio and cost benefit ratio. P. monodon post-larvae were stocked at the rate of 5 nos.m"2 (12 mm; 7 mg) during 1995 and 3 nos.m 2 (15 mm; 10 mg) during 1996. The feeding schedule and other management practices were identical in both the trials. The . shrimps were harvested at the end of 85 days and a production of 732.5 kg.ha"1 (average size: 150 mm; 20 g) was obtained in 1995 and 647.5 kg.ha"1 (average size: 160 mm; 26 g) in 1996.